Respuesta :

Answer:

Step-by-step explanation:

[tex]y = \dfrac{1}{2}*(x - 3)^{2}\\\\\\2y = (x-3)^{2}\\\\\\2y = x^{2}-2*x*3 + 3^{2}\\\\\\2y = x^{2} - 6x + 9 \ --------------(I)[/tex]

y = -x + 7  -------------(II)

Plugin y = -x + 7 in equation (I)

2(-x + 7) =x² - 6x + 9

-2x + 14 =x ² - 6x + 9

x² - 6x + 9 = -2x + 14

x² - 6x  + 9 + 2x - 14 = 0

x² - 4x  - 5 = 0

x² -5x + x - 5 = 0

x(x - 5) + 1(x - 5) = 0

(x -5)(x + 1) = 0

x- 5 = 0 ;   x + 1 = 0

x = 5      ; x = -1

When x = 5  ⇒ y = -5 + 7 = 2

When x = -1 ⇒ y = -(-1) + 7 = 1 + 7 = 8

Solution (5 , 2) & (-1 , 8)

That is the answer , hope this helps.!
Ver imagen emmamadyson1